Gender Mainstreaming in the Danish Central Administration: (Mis)understandings of the Gendered Impact of Law Proposals - Diana Højlund Madsen (The Royal Danish Library, 2018)
Gender mainstreaming is the dominant strategy of the Danish national gender equality efforts. However, gender impact assessments have neither been sufficiently integrated in the policy-making processes of the Danish ministries nor in their organisational cultures, and their impact is minor. Drawing on feminist perspectives on institutional development the article focuses on two case studies – the Ministry of Employment and the Ministry of Transport – with two different practices for doing gender equality assessments. It is important to consider the (lack of) political demand for gender equality assessments in order to understand the (negative) development in terms of their number and content; very few gender equality assessments are produced, and those that are tend to hold little or no transformative potential as they show limited recognition of the gendered consequences of the law proposals.